IMPLEMENTASI KURIKULUM 2013 PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM MENANAMKAN AKHLAKUL KARIMAH SISWA - Fahrudin Fahrudin (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: The purpose of this paper was conducted to describe three things. First, About the planning of learning Islamic Religious Education And Character Curriculum 2013 in an effort to cultivate akhlakul karimah of students in Public Vocational Secondary Schools 1 Pematangsiantar. Based on the research findings obtained that information. First, the planning of learning Islamic Religious Education And Character Curriculum 2013 in the effort to cultivate akhlakul karimah students in Public Vocational Secondary Schools 1 Pematangsiantar done by preparing the steps and material akhlakul karimah on learning planning of Islamic Religious Education And Character which includes; preparation of annual programs, semester programs, weekly and daily programs, and in the preparation of the Lesson Plans (RPP). Second, The process of Learning Islamic Religious Education And Character Curriculum 2013 in effort akhlakul karimah of student cultivation in Public Vocational Secondary Schools 1 Pematangsiantar done with; the implementation of Islamic Religious Education And Character -based characteristic learning, the application of learning with habituation and exemplary approach, guidance of familiarity at the time of learning pree test, akhlakul karimah cultivation on the formation of competence, and akhlak planting at post test. Third, the assessment of learning Islamic Religious Education And Character Curriculum 2013 in an effort to cultivate akhlakul karimah of students in Public Vocational Secondary Schools 1 Pematangsiantar done with authentic assessment that includes assessment of attitude competence, knowledge competency assessment, and skills assessment related to mastery akhlakul karimah.Kata Kunci: Implementasi Kurikulum 2013, Pendidikan Agama Islam dan Budi Pekerti, Akhlakul Karimah Siswa.